The Importance of Religious Counselors in Building Moderate Attitudes in Moderate Villages - Ghandi Ghandi (Yayasan Adra Karima Hubbi, 2024)
Background. Implementing religious moderation in villages is crucial for fostering an understanding of harmonious and non-extreme attitudes within society. This approach helps to maintain social cohesion and prevent conflicts that may arise from radical or extremist views. Purpose. The main goal of this research is to highlight the importance of religious educators in promoting and implementing the values of religious moderation in village communities. By focusing on moderate Islam, the study aims to integrate these values into everyday life through various religious and community activities. Method. This research employs a combination of primary and secondary data. Primary data is collected through interviews with key individuals involved in promoting religious moderation, such as religious educators and community leaders. Secondary data includes documentation and observations conducted during field studies. Results. The study reveals that the values of religious moderation are essential for creating peaceful and balanced community life. Religious instructors play a pivotal role in this process, acting as both leaders and coaches in fostering a moderate Islamic perspective. The research shows that incorporating religious moderation into daily village activities helps to strengthen the community's understanding of these values, reducing the likelihood of extremist behaviors and enhancing social harmony. Conclusion. The findings underscore the importance of religious educators in embedding the principles of religious moderation within village communities. By leveraging their influence and organizing various religious and community events, these educators effectively promote a moderate approach to Islam, contributing to a harmonious and stable society.